REPRESENTASI SPIN DOCTOR DALAM MEMPERBAIKI CITRA PADA FILM WAG THE DOG (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - Eva Lumban Tobing (Universitas Mercu Buana, 2022)
Public Relations (PR) has an important role both for institutions and for external public relations. One of the roles of PR in a company is Problem Solving Facilitator, one of the duties of a PR practitioner in his role as a Problem Solving Facilitator is to create alternatives to solve a problem, not only that, a PR practitioner must also be able to detect signs of an issue before the issue develops into a problem that can damage the image of an institution as well as the image of individuals in an institution. The formulation of the problem in this study is how the representation of a spin doctor in improving the image in the film Wag The Dog. The purpose of this study was to determine the representation of a spin doctor in improving the image of the film Wag The Dog. This study uses a qualitative descriptive approach with a semiotic approach. Charles Sanders Peirce, With the Charles Sanders Peirce semiotics research method, the researcher will analyze through Icons, Indexes, and symbols according to the existing context. It contains communication theories which are generally realized by a Public Relations in carrying out their duties and roles both in organizations and companies.